(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article explores the environmental factors in Tashkent city and their impact on the development of cardiovascular diseases. Nowadays, due to urbanization and industrialization, factors such as air pollution, noise levels, and the urban heat island effect are negatively affecting the health of city residents. During the study, existing statistical data and previous scientific research were analyzed to substantiate the relationship between environmental factors and cardiovascular diseases.